Induction of antitoxin responses in Clostridium-difficile-infected patients compared to healthy blood donors. (October 2016) - von Eichel-Streiber, Alice; Paik, Wonbeom; Knight, Katherine; Gisch, Karina; Nadjafi, Karolina; Decker, Christine; Bosnjak, Oliver; Cheknis, Adam; Johnson, Stuart; von Eichel-Streiber, Christoph
Abstract: According to the literature Clostridium difficile antitoxins are present in up to 66% of humans. In a survey of ∼400 plasma samples from healthy blood donors we found that less than 6% were positive for anti-TcdA or anti-TcdB antitoxins. Using the same standard immunoassay protocol, we looked for IgG and IgA antitoxins in the blood and stool samples from 25 patients with C. difficile infection (CDI). Some patients with CDI had no antitoxin detected at all, while others had high levels of specific IgG- and IgA-antitoxins against both TcdA and TcdB in blood and IgA-anti-TcdA and -anti-TcdB antibodies in stool. Systemic responses to TcdB and mucosal responses to TcdA predominated. Among patients infected with the NAP1/027/BI strain, systemic IgG-anti-TcdB responses were particularly elevated. In contrast, patients infected with non-027 strains had more elevated mucosal IgA-anti-TcdA responses. Furthermore, high titer sera did not correlate with high neutralizing potential. We hypothesize that paradoxical killing of primed B-cells by antibody-mediated endosomal uptake of the Large Clostridial Toxins, TcdA and TcdB leads to clonal elimination of the fittest B-cells. If this hypothesis is confirmed, immune suppression rather than protective humoral immunity might be the consequence in some patients infected with toxigenic C. difficile . Graphical abstract: Highlights: In ≈400 healthy plasma donors only low titer Toxin A and B antibodies were detected. Variable antitoxin response was determined in blood and stool of 25 CDI patients. Systemic response to TcdB and mucosal response to TcdA predominate in CDI patients. High antitoxin titers do not correlate to high neutralization potential. A hypothesis of paradoxical killing of the fittest B-cell by TcdA/B is proposed.